Development of learning videos of atomic theory concepts of Tialo language - Filza Farhana; Sahrul Saehana; Lilia Halim (Universitas PGRI Kanjuruhan Malang, 2021)
The purpose of this research is to produce a video learning content on atomic theory. This research uses the design and development design that employs the ADDIE model. The research instrument used was a questionnaire with a four-likert scale admistered on content experts, linguists, media experts, teachers and 10 students of MA AL-KHAIRAAT Tomini. The validity of the content, language and media aspects was said to be good with scores of 3.25; 3.33 and 3.28 respectively. Meanwhile, the scores obtained from teachers and students of class XI IPA were 3.87 and 3.51, both of which were in the